2022
DOI: 10.2174/1573407217666210903113347
|View full text |Cite
|
Sign up to set email alerts
|

Uncaria tomentosa (Willd. ex Schult.): Focus on Nutraceutical Aspects

Abstract: : Medicinal plants have been globally exploiting as an alternative to chemical drugs in the treatment of several diseases due to low unwanted side effects, environmentally friendly nature and low production costs, therefore, it is important to analyze the therapeutic properties of various medicinal plants to understand their potential bioactivity. Uncaria tomentosa is one of these medicinal plants with many health-promoting effects. Although the geographical resources of cat's claw go back to the remote tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…This process involves a variety of immune cell types, particularly cytotoxic T cells 24 , natural killer cells 25 , and cytokines like tumour necrosis factor-α and chemokines 26 . According to reports from many parts of the world, medicinal herbs like Glycyrrhiza glabra 27 , Uncaria tomentosa 28 , Camellia sinensis 29 , Panax ginseng 30 , Prunus armenaica (apricot) 31 , Allium sativum 32 , Arctium lappa 33 , and Curcuma longa have a significant potential to treat cancer 34 . Fascinating research results have revealed that the primary components of these plants that are responsible for the anticancer effects are bioactive immunomodulators.…”
Section: Role Of Immune Modulation In Gastric Cancermentioning
confidence: 99%
“…This process involves a variety of immune cell types, particularly cytotoxic T cells 24 , natural killer cells 25 , and cytokines like tumour necrosis factor-α and chemokines 26 . According to reports from many parts of the world, medicinal herbs like Glycyrrhiza glabra 27 , Uncaria tomentosa 28 , Camellia sinensis 29 , Panax ginseng 30 , Prunus armenaica (apricot) 31 , Allium sativum 32 , Arctium lappa 33 , and Curcuma longa have a significant potential to treat cancer 34 . Fascinating research results have revealed that the primary components of these plants that are responsible for the anticancer effects are bioactive immunomodulators.…”
Section: Role Of Immune Modulation In Gastric Cancermentioning
confidence: 99%